Clinical study of an orbital epithesis supported by osseointegrated implants - NOSAKA, Yasuhiro; HONDA, Masaki; SAWAI, Toshihiro; WATANABE, Kazuyo; NAKAI, Hidetaka; OZEKI, Kenji; FUJIMOTO, Takehiro; NIIMI, Atsushi; UEDA, Minoru (Japanese Journal of Oral and Maxillofacial Surgery, 1996)
Orbital defects associated with malignant tumor surgery or trauma can be socially disabling because of cosmetic factors. We used osseointegrated implants to support orbital epitheses in 6 patients. In this paper we showed the effectiveness of this treatment and examined the following points: 1. Period of treatment. 2. Success rate of implants placed in irradiated bone. 3. Placement site of implants. 4. Skin reactions around abutments. 5. Retention and fixation of epitheses.